30.3: The world's first prototype of 85‐inch 8K4K 120Hz LCD with BCE‐IGZO structure and GOA design. (28th November 2018) - Zhao, Ying-Chun; Zhao, Feng; Chang, CK; Chiu, Chung-Yi; RAY,; Shi, Long-Qiang; Ge, Shi-Min; Kong, Zeng-Jie; Deng, Tong-Shuai; Xu, Feng-Cheng; Du, Peng
Abstract : We have developed a 85‐in. 120Hz‐Driven 8%4% VA‐LCD which succesfully applied BCE IGZO in GOA to gain super resolution, ultra ‐ high refresh rate for the first time in the world .